2011
DOI: 10.1161/circimaging.110.963280
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Evaluation Before Bidirectional Glenn Operation in Functional Single-Ventricle Heart Disease

Abstract: Background-Cardiac catheterization is routinely performed in patients with single ventricle before bidirectional Glenn operation (BDG). There is interest in noninvasive evaluation alone before BDG, but concern for echocardiography successfully imaging the relevant anatomy persists. We evaluated the accuracy of echocardiographic imaging of vascular anatomy. Methods and Results-Diagnostic images of 130 patients who had echocardiography and catheterization before BDG were reviewed; diameters of the pulmonary arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…The fact that Fontan patients have typically undergone multiple surgical procedures involving these structures likely contributes to the difficulty in imaging these structures. However, imaging of the pulmonary arteries has also proven challenging even in younger patients with single ventricle physiology prior to the superior cavopulmonary anastomosis, or stage II procedure 10 . Other investigators have shown that these structures are difficult to image using echocardiography in the post-Fontan population, and that cardiac magnetic resonance imaging is superior to echocardiography in the noninvasive evaluation of these specific structures 1113 .…”
Section: Discussionmentioning
confidence: 99%
“…The fact that Fontan patients have typically undergone multiple surgical procedures involving these structures likely contributes to the difficulty in imaging these structures. However, imaging of the pulmonary arteries has also proven challenging even in younger patients with single ventricle physiology prior to the superior cavopulmonary anastomosis, or stage II procedure 10 . Other investigators have shown that these structures are difficult to image using echocardiography in the post-Fontan population, and that cardiac magnetic resonance imaging is superior to echocardiography in the noninvasive evaluation of these specific structures 1113 .…”
Section: Discussionmentioning
confidence: 99%
“…Stern et al [5] showed that in patients being evaluated for a bidirectional Glenn procedure (the second to last stage in surgical palliation for single ventricle (SV) anatomy) that echocardiography had only 59 % agreement in the presence or absence of pulmonary branch stenosis. The actual percentage, of course, depended on institution experience and protocol.…”
Section: Echocardiographymentioning
confidence: 99%
“…Abnormal ventricular function is a predictor of morbidity and mortality in patients with single ventricle physiology . However, applying conventional echocardiographic measurements of ventricular function, such as ejection fraction, in patients with single ventricle physiology can be difficult given their variable and unique ventricular geometry . Frequently, clinicians must rely on their subjective assessment of function, which suffers from poor observer variability.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, applying conventional echocardiographic measurements of ventricular function, such as ejection fraction, in patients with single ventricle physiology can be difficult given their variable and unique ventricular geometry. [2][3][4][5] Frequently, clinicians must rely on their subjective assessment of function, which suffers from poor observer variability. Cardiologists are left with the daunting challenge of managing a population at high risk for heart failure without validated, objective echocardiographic indices of cardiac function.…”
Section: Introductionmentioning
confidence: 99%